Analysis of Human Placental Tissues Using Gas Chromatography High Resolution Accurate Mass Spectrometry to Characterize Exposure to a Range of Semivolatile Organic Compounds - Michelle Misselwitz; Nicholas J. Herkert; P. Lee Ferguson; Heather M. Stapleton (Exposure and Health, 2026)

Associations of serum PFAS with COVID-19 antibody levels among fully vaccinated adults - Rachel A. Bauer; Zhao Yang; Michael Petriello; Sharon Zhang; Heather M. Stapleton; John L. Adgate; Courtney C. Carignan (Environmental Research, 2026)

Associations between exposure to polycyclic aromatic hydrocarbons and biomarkers of acute kidney injury among Chilean agricultural workers - Grant D. Tore; Melissa DeSantiago; Heather M. Stapleton; Wassim Obeid; Chirag R. Parikh; Jordan R. Kuiper; Margarita Valenzuela; Catterina Ferreccio; Louis Fazen; Aisha S. Dickerson; Sandra Cortés; Lesliam Quirós-Alcalá (International Journal of Hygiene and Environmental Health, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Developmental PBDE exposure persistently impairs mast cell function in vivo and drives sex-specific morphological and transcriptional changes in bone marrow–derived mast cells - Jared Franges; Lauren Malinowski; Chathuri De Alwis; Taylor Doolittle; Yixing Li; Hannahlee Dixon; Yang Tang; Helen Watson; Jasmine Peace; Dereje Jima; Leslie Sombers; Gregory McCarty; et al. (Environmental Research, 2026)

The utility of silicone wristbands in characterizing exposure to parabens found in commercial lotions - Jessica L. Levasseur; Kate Hoffman; Sharon Zhang; Heather M. Stapleton (Science of The Total Environment, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Children’s exposure to chemical contaminants: Demographic disparities and associations with the developing basal ganglia - Carina H. Fowler; Aaron Reuben; Heather M. Stapleton; Kate Hoffman; Nicholas Herkert; Lubna Barakat; Michael S. Gaffrey (Environmental Research, 2024)

Associations of environmental chemical exposures measured in personal silicone wristbands with sociodemographic factors, COVID-19 restrictions, and child respiratory health - Brennan H. Baker; Drew B. Day; Marnie F. Hazlehurst; Nicholas J. Herkert; Heather M. Stapleton; Sheela Sathyanarayana (Environmental Research, 2024)

Silicone wristbands reveal ubiquitous human exposure to ortho-phthalates and non-ortho-phthalate plasticizers in Southern California - Aalekhya Reddam; Nicholas Herkert; Heather M. Stapleton; David C. Volz (Environmental Research, 2024)

Advancing Understanding of Chemical Exposures and Maternal-child Health Through the U.S. Environmental Influences on Child Health Outcomes (ECHO) Program: A Scoping Review - Emily S. Barrett; Jennifer L. Ames; Stephanie M. Eick; Alicia K. Peterson; Zorimar Rivera-Núñez; Anne P. Starling; Jessie P. Buckley; Barbara O‟Brien; Lisa Peterson; Patrick Parsons; Kannan Kurunthacalam; Manish Arora; et al. (Current Environmental Health Reports, 2024)
Purpose of Review Environmental chemical exposures may disrupt child development, with long-lasting health impacts. To date, U.S. studies of early environmental exposures have been limited in size and diversity, hindering power and generalizability. With harmonized data from over 60,000 participants representing 69 pregnancy cohorts, the National Institutes of Health’s Environmental influences on Child Health Outcomes (ECHO) Program is the largest study of U.S. children’s health. Here, we: (1) review ECHO-wide studies of chemical exposures and maternal-child health; and (2) outline opportunities for future research using ECHO data. Recent Findings As of early 2024, in addition to over 200 single-cohort (or award) papers on chemical exposures supported by ECHO, ten collaborative multi-cohort papers have been made possible by ECHO data harmonization and new data collection. Multi-cohort papers have examined prenatal exposure to per- and polyfluoroalkyl substances (PFAS), phthalates, phenols and parabens, organophosphate esters (OPEs), metals, melamine and aromatic amines, and emerging contaminants. They have primarily focused on describing patterns of maternal exposure or examining associations with maternal and infant outcomes; fewer studies have examined later child outcomes (e.g., autism) although follow up of enrolled ECHO children continues. The NICHD’s Data and Specimen Hub (DASH) database houses extensive ECHO data including over 470,000 chemical assay results and complementary data on priority outcome areas (pre, peri-, and postnatal, airway, obesity, neurodevelopment, and positive health), making it a rich resource for future analyses. Summary ECHO’s extensive data repository, including biomarkers of chemical exposures, can be used to advance our understanding of environmental influences on children’s health. Although few published studies have capitalized on these unique harmonized data to date, many analyses are underway with data now widely available.

Children's exposure to brominated flame retardants in the home: The TESIE study - Kate Hoffman; Xuening Tang; Ellen M. Cooper; Stephanie C. Hammel; Andreas Sjodin; Allison L. Phillips; Thomas F. Webster; Heather M. Stapleton (Environmental Pollution, 2024)

Chemical uptake into silicone wristbands over a five day period - Samantha M. Samon; Kate Hoffman; Nicholas Herkert; Heather M. Stapleton (Environmental Pollution, 2024)

Investigating sensitization activity of azobenzene disperse dyes via the Direct Peptide Reactivity Assay (DPRA) - Kirsten E. Overdahl; Robert M. Tighe; Heather M. Stapleton; P. Lee Ferguson (Food and Chemical Toxicology, 2023)

Characterizing azobenzene disperse dyes and related compounds in house dust and their correlations with other organic contaminant classes - Kirsten E. Overdahl; Christopher D. Kassotis; Kate Hoffman; Gordon J. Getzinger; Allison Phillips; Stephanie Hammel; Heather M. Stapleton; P. Lee Ferguson (Environmental Pollution, 2023)

Measuring semi-volatile organic compound exposures during pregnancy using silicone wristbands - Samantha Samon; Nicholas Herkert; Akhgar Ghassabian; Hongxiu Liu; Stephanie C. Hammel; Leonardo Trasande; Heather M. Stapleton; Kate Hoffman (Chemosphere, 2023)

PFAS levels in paired drinking water and serum samples collected from an exposed community in Central North Carolina - Samantha M. Hall; Sharon Zhang; George H. Tait; Kate Hoffman; David N. Collier; Jane A. Hoppin; Heather M. Stapleton (Science of The Total Environment, 2023)

Triphenyl phosphate-induced pericardial edema in zebrafish embryos is reversible following depuration in clean water - Jenna Wiegand; John Hoang; Sarah Avila-Barnard; Charvita Nemarugommula; Megan Ha; Sharon Zhang; Heather M. Stapleton; David C. Volz (Aquatic Toxicology, 2023)

Brominated flame retardants and legacy organochlorines in archived human placenta samples: Sex differences, temporal analysis and associations with infant birth weight. - Matthew Ruis; Kate Hoffman; Heather M. Stapleton (Chemosphere, 2023)

Hormone receptor activities of complex mixtures of known and suspect chemicals in personal silicone wristband samplers worn in office buildings - Anna S. Young; Nicholas Herkert; Heather M. Stapleton; Brent A. Coull; Russ Hauser; Thomas Zoeller; Peter A. Behnisch; Emiel Felzel; Abraham Brouwer; Joseph G. Allen (Chemosphere, 2023)

Persistent autism-relevant behavioral phenotype and social neuropeptide alterations in female mice offspring induced by maternal transfer of PBDE congeners in the commercial mixture DE-71 - Elena V. Kozlova; Matthew C. Valdez; Maximillian E. Denys; Anthony E. Bishay; Julia M. Krum; Kayhon M. Rabbani; Valeria Carrillo; Gwendolyn M. Gonzalez; Gregory Lampel; Jasmin D. Tran; Brigitte M. Vazquez; Laura M. Anchondo; et al. (Archives of Toxicology, 2022)
Polybrominated diphenyl ethers (PBDEs) are ubiquitous persistent organic pollutants (POPs) that are known neuroendocrine disrupting chemicals with adverse neurodevelopmental effects. PBDEs may act as risk factors for autism spectrum disorders (ASD), characterized by abnormal psychosocial functioning, although direct evidence is currently lacking. Using a translational exposure model, we tested the hypothesis that maternal transfer of a commercial mixture of PBDEs, DE-71, produces ASD-relevant behavioral and neurochemical deficits in female offspring. C57Bl6/N mouse dams (F0) were exposed to DE-71 via oral administration of 0 (VEH/CON), 0.1 (L-DE-71) or 0.4 (H-DE-71) mg/kg bw/d from 3 wk prior to gestation through end of lactation. Mass spectrometry analysis indicated in utero and lactational transfer of PBDEs (in ppb) to F1 female offspring brain tissue at postnatal day (PND) 15 which was reduced by PND 110. Neurobehavioral testing of social novelty preference (SNP) and social recognition memory (SRM) revealed that adult L-DE-71 F1 offspring display deficient short- and long-term SRM, in the absence of reduced sociability, and increased repetitive behavior. These effects were concomitant with reduced olfactory discrimination of social odors. Additionally, L-DE-71 exposure also altered short-term novel object recognition memory but not anxiety or depressive-like behavior. Moreover, F1 L-DE-71 displayed downregulated mRNA transcripts for oxytocin ( Oxt ) in the bed nucleus of the stria terminalis (BNST) and supraoptic nucleus, and vasopressin ( Avp ) in the BNST and upregulated Avp1ar in BNST, and Oxtr in the paraventricular nucleus. Our work demonstrates that developmental PBDE exposure produces ASD-relevant neurochemical, olfactory processing and behavioral phenotypes that may result from early neurodevelopmental reprogramming within central social and memory networks.

Organophosphate Esters: Are These Flame Retardants and Plasticizers Affecting Children’s Health? - Brett T. Doherty; Stephanie C. Hammel; Julie L. Daniels; Heather M. Stapleton; Kate Hoffman (Current Environmental Health Reports, 2019)

Using laboratory-generated biosolids to evaluate the microbial ecotoxicity of triclosan in a simulated land application scenario - Ryan M. Holzem; Courtney M. Gardner; Heather M. Stapleton; Claudia K. Gunsch (Environmental Science and Pollution Research, 2018)

Genotoxicity in Atlantic killifish (Fundulus heteroclitus) from a PAH-contaminated Superfund site on the Elizabeth River, Virginia - Dawoon Jung; Cole W. Matson; Leonard B. Collins; Geoff Laban; Heather M. Stapleton; John W. Bickham; James A. Swenberg; Richard T. Di Giulio (Ecotoxicology, 2011)